Formation of the rete testis during mouse embryonic development. Issue 12 (14th September 2020) - Kulibin, Andrey Yu.; Malolina, Ekaterina A.
Abstract: Background: The rete testis connects seminiferous tubules of the testis with efferent ducts having a mesonephric origin. The development of the rete testis is insufficiently studied, but there is evidence suggesting that it originates from gonadal cells. Here, the formation of the rete testis was investigated from E11.5 to E16.5 using immunofluorescent staining and 3D‐modeling. Results: The rete testis became visible by SOX9 and PAX8 staining starting from E12.5. It was located in the mesonephros but connected with testis cords formed by Sertoli cells expressing SOX9, AMH, DMRT1. Between E13.5 and E14.5, AMH+ network of testis cords at the mesonephric side began to disintegrate in a gradient‐dependent manner along the anterior‐posterior axis of the gonad and connections between testis cords gradually lost AMH becoming a part of the rete. Cells combining features of Sertoli and rete cells (PAX8+ AMH+ and DMRT1+ AMH− cells) were detected starting from E14.5, suggesting that some rete cells originated from Sertoli cells. The rete ovarii, a female counterpart of the rete testis, developed in a similar way as the rete testis until E13.5. Conclusions: A part of the rete testis originates from connections between testis cords. Evidence that Sertoli cells contribute to rete cells is provided. Key Findings: The development of the rete testis was examined using immunofluorescent staining and 3D modelling. The proximal part of the rete testis is derived from the network of testis cords. Cells combining features of Sertoli and rete cells appear at the mesonephric border of the testis as early as E14.5.